2020
DOI: 10.3390/diagnostics10040183
|View full text |Cite
|
Sign up to set email alerts
|

A Finite Element Analysis Study from 3D CT to Predict Transcatheter Heart Valve Thrombosis

Abstract: Background: Transcatheter aortic valve replacement has proved its safety and effectiveness in intermediate- to high-risk and inoperable patients with severe aortic stenosis. However, despite current guideline recommendations, the use of transcatheter aortic valve replacement (TAVR) to treat severe aortic valve stenosis caused by degenerative leaflet thickening and calcification has not been widely adopted in low-risk patients. This reluctance among both cardiac surgeons and cardiologists could be due to concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…It is important to underline that unlike the standard aortic valve replacement, which allows the complete removal of calcifications, in the percutaneous procedure the calcifications are pressed against the aortic wall. The postoperative CT scan fails to show these calcifications [ 11 , 12 ]. Prosthetic stent deformation of both self-expandable and balloon-expandable devices was noted as a consequence of these calcifications, which caused a high degree of mismatch between the native aortic root wall and the stent profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to underline that unlike the standard aortic valve replacement, which allows the complete removal of calcifications, in the percutaneous procedure the calcifications are pressed against the aortic wall. The postoperative CT scan fails to show these calcifications [ 11 , 12 ]. Prosthetic stent deformation of both self-expandable and balloon-expandable devices was noted as a consequence of these calcifications, which caused a high degree of mismatch between the native aortic root wall and the stent profile.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested the role of complex native calcifications of the aortic valve in the occurrence of these complications [ 7 , 8 ]. However, the computed tomography (CT) imaging modalities routinely used in the perioperative work-up for TAVR have proven unable to clearly identify all the anatomical parameters or characteristics predicting the risk of occurrence of device complications [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-uniform expansion related to extensive calcifications is responsible for prosthetic device deformation that leads to an eccentricity > 10%, resulting in incomplete expansion of the metallic frame at almost all levels. In a fatigue simulation study, transcatheter valve leaflets were noted to sustain higher stresses, strains, and fatigue damage than did surgical aortic valve leaflets [ 60 ] . Finally, prosthetic valve thrombosis is considered a marker for SVD, and recent echocardiographic data from PARTNER-3 corroborated these concerns, observing leaflet thrombosis as the main cause of SVD at 1 year [ 52 ] .…”
Section: Prosthetic Valve Thrombosismentioning
confidence: 99%
“…Different TAV frame designs could be investigated as well. Finally, FE simulations could be coupled with computation fluid dynamics simulations, following device implantation, in order to address TAV implantation procedural complications such as PVL (De Jaegere et al 2016;Mao et al 2018;Rocatello et al 2019) and thrombosis (Bianchi et al 2019;Nappi et al 2020).…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%